Ambiguity of Interpretation in The Criminal Act of Contempt of State Institutions in The Potential Criminal Acts of Abuse of Power - Wahyuono, Firman Tri; Munawar, Said; Luhukay, Roni Sulistyanto (Kadiri Islamic University, 2026)
This study examines the ambiguity of interpretation in the criminal act of contempt of state institutions in the context of potential criminal acts of abuse of power. The method used is legal research. The results show that democracy requires the guarantee of freedom of expression as a basis for public participation and a mechanism for controlling power. In this context, the criminal act of insulting state institutions becomes problematic when formulated in a multi-interpretive manner and does not comply with the principles of legality and lex certa. The ambiguity of the element of